PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI INTEGRITAS SEBAGAI VARIABEL INTERVENING PADA KARYAWAN BANK BNI CABANG RAWAMANGUN - Esti, E; Padmowiharjo, Soedijanto; Tabroni (SEKOLAH PASCASARJANA PRESS, 2019)
This study aims to determine the effect of transformational leadership and compensation on employees' integrity and performance at Bank BNI. The method used in this study was descriptive method with a quantitative approach. The population in this study was all employees in the BNI Bank Rawamangun branch totaling to 360 people, and the sample was 190 respondents from the number of employees. The data analysis technique used is structural equation modeling (SEM) by using Lisrel. The results showed that transformational leadership has a positive effect on integrity, compensation has a positive effect on integrity, transformational leadership has a positive effect on employee performance, compensation has a positive effect on employee performance, integrity has a positive effect on employee performance, transformational leadership has a positive effect on employee performance through integrity, and compensation has a positive effect on employee performance through integrity.